Endocrine outcome in children with medulloblastoma treated with 18 Gy of craniospinal radiation therapy - Xu, Weizhen (Duke University Press, 2004)
Craniospinal radiation therapy (CSRT) combined with chemotherapy results in significant endocrine morbidity. Between 1987 and 1990, a trial using 18 Gy was conducted to treat 10 young children with medulloblastoma. There were 7 survivors. We compared the endocrine outcome in these children (group 18 Gy) to that of a comparable group treated with conventional doses of CSRT that ranged from 23 to 39 Gy (group CD). Both groups had an identical history of chemotherapy and tumor stage and were treated with recombinant growth hormone therapy (rhGH). The mean age of group 18 Gy at diagnosis was 4.0 years, and rhGH treatment was initiated in 6 children at age 9.2 years. Group CD (12 children) was diagnosed at a mean age of 5.8 years and rhGH started in 11 children at a mean age of 9.6 years. The dose of rhGH used in both groups was identical (0.3 mg/kg/wk). For group 18 Gy, adult heights and sitting heights (a mean standard deviation score of −1.01 ± 1.11 and −1.62 ± 1.16, respectively) were statistically greater (P < 0.05) than those for group CD (mean standard deviation score of −2.04 ± 0.83 and −3.16 ± 1.43, respectively). Moreover, adult heights of group 18 Gy were not different from midparental heights, unlike group CD, whose adult heights were less than midparental heights (P < 0.0001). Of other endocrine sequelae, 10 patients of the CD group were hypothyroid, 3 had adrenal insufficiency, 3 had hypogonadism, and 2 had early puberty. In contrast, within group 18 Gy, only 1 was hypothyroid (P = 0.006) and 1 had early puberty. We conclude that endocrine morbidity was significantly reduced with 18 Gy CSRT in young children with medulloblastoma.